Pengaruh Metanol dalam Produksi Biodiesel dari Tamanu Oil Menggunakan Katalis Lipase - Martha Aznury; Ahmad Zikri; Robert Junaidi; Marieska Lupikawaty; Chintia Oktariyensi (JURNAL SELULOSA, 2022)
Biodiesel is a fuel derived from renewable sources, wich can be used efficiently in petrodiesel engines. This study aims to produce biodiesel from tamanu oil enzymatically using the lipase enzyme. This enzimatic method has a high value product made during the production of biodiesel. Biodiesel production through the transesterification process with methanol reactant and alkaline catalysts has many weaknesses, namely the presence of a saponification reaction and it is difficult to separate because the catalyst is homogeneus. The result of this study indicate that tamanu oil has been seccessfully converted into biodiesel with an optimum oil : methanol molar ratio of 1:5 and a yield precentage of 87,67% with a methyl ester content of 97,37%